Prevalensi Gangguan Fungsi Pendengaran Akibat Kebisingan Lingkungan Kerja pada Pekerja Kayu di Desa Mas Kecamatan Ubud Kabupaten Gianyar - Adnyani, Ayu Luih; Adiputra, Luh Made Indah Sri Handari (E-Jurnal Medika Udayana; Vol 6 No 12 (2017): E-Jurnal Medika Udayana, 2017)
Every workplace had its own potential to cause disruption for workers that would affected their health and was unable to work optimally . The impact affected the function of human hearing, which is Noise Induced Hearing Loss due to noise exposure in the workplace. This study aimed to determine the prevalence of workers with hearing loss or decrease in hearing function. This study uses an observational study design with cross sectional approach which meant that all the variables studied, measured, observed only one time, at one time and could find out the prevalence of wood workers who have a hearing loss. This study uses several tools that otoscope and audiometer were performed on 36 samples of wood workers. Workers with noise intensity 94.0 to 103.4 dB audiometry examination has been carried out on 36 samples obtained 10 have a hearing loss ranging from mild to very severe. Mild 6 (16.7 %), severe 1 (2.8 %), and very severe 3 (8.3 %) . Ages ranged from 18 to 50 years of work experience ranging from 1 to 12 years. Age and length of employment played a role in the occurrence of hearing loss, increasing age is generally followed by decrease in  auditory function coupled with noise exposure on an ongoing basis. In this study, more workers aged over 30 years, long exposure to the most widely ranging from 1 up to 3 years and is followed by 7 to 12 years. Then, long work and age may be a risk factor accelerating auditory dysfunction. Keyword : Hearing loss, noise, audiometry.